2022
DOI: 10.3390/d14020148
|View full text |Cite
|
Sign up to set email alerts
|

A PCR-Based Retrospective Study for Beak and Feather Disease Virus (BFDV) in Five Wild Populations of Parrots from Australia, Argentina and New Zealand

Abstract: The beak and feather disease virus (family Circovirdae) is a virus of concern in the conservation of wild Psittaciformes globally. We conducted a PCR screening for the beak and feather disease virus (BFDV) using samples collected during previous field studies (1993–2014) in five populations of parrots of the Southern Hemisphere: Eclectus parrots (Eclectus roratus) and Crimson rosellas (Platycercus elegans) from Australia, Burrowing parrots (Cyanoliseus patagonus) and Monk parakeets from Argentina (Myiopsitta m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Rainbow Lorikeets were another commonly admitted species with diagnoses ranging from trauma, injury (broken wings or legs) or suspected BFD which is related with chronic stress and usually results in high rates of mortality. BFD is a disease caused by the beak and feather disease virus (BFDV), a DNA virus that predominantly infects wild Psittaciformes population, resulting in immune-suppression, feather loss, weight loss, anaemia and other tissue damages (Ortiz-Catedral et al, 2022). Our results suggest that lorikeet species showed high rate of BFD (34.38% of Rainbow Lorikeets and 26.79% of Musk Lorikeets were diagnosed as BFD), making BFD is a non-negligible stressor and health risk for the wild bird populations.…”
Section: Discussionmentioning
confidence: 99%
“…Rainbow Lorikeets were another commonly admitted species with diagnoses ranging from trauma, injury (broken wings or legs) or suspected BFD which is related with chronic stress and usually results in high rates of mortality. BFD is a disease caused by the beak and feather disease virus (BFDV), a DNA virus that predominantly infects wild Psittaciformes population, resulting in immune-suppression, feather loss, weight loss, anaemia and other tissue damages (Ortiz-Catedral et al, 2022). Our results suggest that lorikeet species showed high rate of BFD (34.38% of Rainbow Lorikeets and 26.79% of Musk Lorikeets were diagnosed as BFD), making BFD is a non-negligible stressor and health risk for the wild bird populations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, damage in Barcelona ranges from 0.4% to 37% crop loss, depending on the particular crop (Senar et al, 2016). Lastly, recent research indicates that monk parakeets may serve as a reservoir for zoonotic diseases in some areas (Morinha et al, 2020), introducing a concern for human health; however, this is not widely observed (Ortiz-Catedral et al, 2022). As a result of these concerns and conflicts, monk parakeets have become a management priority in many areas.…”
Section: Introductionmentioning
confidence: 99%
“…Chlamydia but not beak and feather disease virus (BFDV) in Brazil [14]. A retrospective study also failed to find BFDV in Australia, Argentina, and New Zealand [15], while a new BFDV genotype has recently been found in non-native Spanish parakeet populations [16], and a three-decade study investigated the diversification of this virus and the subsequent waves of infection in Mauritius [17]. Moreover, satellite telemetry of even a few individuals revealed information highly relevant to the conservation of a macaw species in Bolivia [18], and a study of the foraging ecology of another species in Argentina revealed once again the important seed dispersal role of parrots for key plants in the ecosystems where they live [19].…”
mentioning
confidence: 99%